The concept of God (Allah) and the unity of God (tawhid) in Islamic worldview - Ashimi, Tijani Ahmad (RSIS International, 2025)
ABSTRACT The concepts of God (Allah) and the unity of God (Tawhid) are extremely important in Muslim life and in Islamic worldview at large. Because God (Allah) and the unity of God(Tawhid) are both the backbone and the main theme of Islam, moreover, they are like two pairs of scissors which are usually used interchangeably in Islamic worldview. Therefore, in Islam the concept of unity of God (Tawhid) is closely related to the expression of “ La Ilaaha Illa Allah” which means there is no god But Allah. It implies that Islam is uncompromising sort of monotheism that believes in One God Who does not have a son and Who is not begotten. It also means Allah is the absolute God that causes the existence of all creations. Therefore, the affirmation of Tawhid by Muslims is compulsory in every aspect of their life, and that affirmation can refrain them from committing sins and evils, simply because the unity of God(Tawhid) is strongly related to oneness of Allah as the Most omnipotent and the Most omniscience. Au contraire to unity of God (Tawhid) is polytheism (Shirk) that implies ascribing partners to Allah or ascribing divine attributes to other besides Allah. Therefore, in Islamic worldview, this act is a very dangerous belief and heinous deed that the person who involves in polytheism will never be forgiven by Almighty Allah (S.W). Based on the above fact, this article aims to explore the concept of God ( Allah), Unity of God (Tawhid) and its different kinds. Then, the article discusses the impacts of Tawhid in human life. However, in order to achieve the aims of this article , the Quranic approach is applied, that is by exploring the concept of God and the unity of God from the Quranic epistemology.Finanlly, a brief conclusion is followed.. Keywords: Allah, Tawhid, Islam, Qur’an Essence, Attributes,